What is the best scale for detecting neurodevelopmental disorders in children with congenital heart disease? A systematic review - Joana Morena Carvalho Nascimento; Eneida Yuri Suda; Evelim Leal de Freitas Dantas Gomes (Elsevier, 2024)
Congenital heart disease (CHD) is a term for a heterogeneous group of abnormalities in cardiac morphogenesis present at birth. Early diagnosis and proper care reduce the mortality rate, directing the concern toward morbidities, such as neurodevelopmental disorders, which can compromise cognitive abilities, communication, social interaction and behaviors as well as cause the delayed acquisition of motor skills and executive functions. To date, there is no scale specifically designed to assess neurodevelopment in CHD. OBJECTIVE: To identify if there was a better scale to assess neurodevelopment in children with CHD up to two years of age. METHODS: A systematic review was performed to investigate the use of five neurodevelopment assessment scales in this population. Searches were conducted in the Embase, MedLine, Cochrane Library, SciELO, LILACS, Scopus and Web of Science databases. RESULTS: A total of 1048 articles were identified and 40 were included in the review. The articles were published between 1982 and 2022. For the General Movement Assessment (GMA), the absence of 'fidgety movements' seems to have a good predictive value for abnormal results at older ages. The Bayley-III scale is recommended for use in this population. CONCLUSION: Most of the included studies opted for the Bayley scale as the main tool for assessing neurodevelopment. Compared to the other most used scales, Bayley III can identify changes in different domains, which directs the treatment. Short Abstract: Neurodevelopmental disorders are common in patients with congenital heart disease both before and after surgery. There are validated instruments that can detect changes in the trajectory of neurodevelopment, it is important to know which is the most appropriate for this population.